Assessing Academic Website Quality Using the WebQual 4.0 Framework - Pakpahan, Jonathan; Meiriza, Allsela; Novianti, Hardini (Politeknik Negeri Batam, 2026)
The rapid growth of digital technologies in higher education has encouraged universities to improve academic service delivery through integrated online platforms. This study aims to measure the quality of the E-PPT (Pusat Pelayanan Terpadu Berbasis Elektronik) website of the Faculty of Computer Science, Universitas Sriwijaya, using the WebQual 4.0 model. A quantitative descriptive method was adopted, involving 354 valid respondents drawn from a total faculty population of 3,058 students across four academic levels (Diploma, Undergraduate, Master’s, and Doctoral). Data were collected via an online survey and analyzed using Microsoft Excel and SPSS. The website achieved an overall mean score of 3.60, indicating a good level of quality. Information Quality showed the highest performance (3.68), followed by Usability (3.58) and Service Interaction Quality (3.56). A supplementary correlation analysis also confirmed positive associations among the WebQual dimensions and overall website quality. These results suggest that the website delivers accurate information and is easy to use, although improvements are needed in responsiveness and interaction quality.